2007
DOI: 10.1590/s0100-204x2007000200008
|View full text |Cite
|
Sign up to set email alerts
|

Green manure incorporation timing for organically grown broccoli

Abstract: -The objective of this work was to determine the effect of incorporation timing of the velvet bean (Stizolobium cinereum) (GM) on both organic broccoli yield and N status. Mineral N content in the soil, biologically fixed N recovery by broccoli, GM biomass decomposition and N release kinetics were also determined. Plots were fertilized with 12 Mg ha -1 of organic compost and received GM either at 0, 15, 30 or 45 days after transplant. Other treatments were compost (12 or 25 Mg ha -1 ), GM, mineral fertilizers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
1
15
1
7
Order By: Relevance
“…The T 1/2 of N-Cj at 33.3 days is close to the results reported in the literature of 24 days (Diniz et al, 2007) and 28 days (Ribas et al, 2010) for gray velvet bean; 30, 56 and 32 days were reported for forage peanut, tropical kudzu and siratro, respectively (Espindola et al, 2006); and more than 15 days for C. juncea (Perin et al, 2006). Since 53% of the N is accumulated between February and May, during coffee bean development (Laviola et al, 2008), there may have been synchrony between C. juncea applied on January 29 and mineralization of 50 and 69.1% of N, respectively, in the first and second month of bean development.…”
Section: Juncea Decompositionsupporting
confidence: 89%
“…The T 1/2 of N-Cj at 33.3 days is close to the results reported in the literature of 24 days (Diniz et al, 2007) and 28 days (Ribas et al, 2010) for gray velvet bean; 30, 56 and 32 days were reported for forage peanut, tropical kudzu and siratro, respectively (Espindola et al, 2006); and more than 15 days for C. juncea (Perin et al, 2006). Since 53% of the N is accumulated between February and May, during coffee bean development (Laviola et al, 2008), there may have been synchrony between C. juncea applied on January 29 and mineralization of 50 and 69.1% of N, respectively, in the first and second month of bean development.…”
Section: Juncea Decompositionsupporting
confidence: 89%
“…The decomposition processes of the green manure and the mineralization of N may be directly related to the amount of mass factor, and therefore to the amount of applied N. It is important to consider beforehand that not all N applied via green manure will be available to crop (Diniz et al, 2007;Matos et al, 2008), even when applied in quantity greater than the recommended dose, especially in the case of short-cycle crop, such as vegetable products. A part of this green manure-N remains in the plant material until full mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…However, the presence of N-biological fixation from subsequent green manure crops is small. The percentage of legume-N absorbed by crops varies from 12.45% to 22.9% of the total N derived from biological fixation (Castro et al, 2004;Silva et al, 2006;Diniz et al, 2007) and reaches about 20% of the total N applied as green manures (Scivittaro et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…In a study with residues of different cover crops, Diniz et al (2007) observed that the application of 8.6 t ha -1 of dry biomass of gray mucuna and 12.0 t ha -1 of organic compost increased mineral N content in the soil, which consequently led to higher yield of broccoli.…”
Section: Broccoli (Brassica Oleracea Var Italica)mentioning
confidence: 99%